Study of perinatal outcome of foetuses with nuchal cord - Inamdar, Misbah M.; Patil, Asmita N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Entanglement of the umbilical cord around the foetal neck (nuchal cord) is a common finding at delivery, but its clinical relevance is not entirely clear. Nuchal cords have generally been considered to be rather benign. However, the insufficiency in data regarding the role of nuchal cord in foetal morbidity and mortality is a source of anxiety and frustration to both parturient and healthcare professionals. Considering the above facts the present study was taken up to establish the incidence of nuchal cord at delivery in the existing setup. Methods: This was a cross sectional comparative study conducted over a period of one year from May 2013 to April 2014. A total of 362 women were selected for the study. These women were briefed about the nature of the study and a written informed consent was obtained. The demographic data and obstetrical history were documented on predesigned proforma. The data obtained was analysed using percentages and comparison done using chi-square test for discrete variables. Results: Incidence of Nuchal Cord was 17.7% among study cases. Based on this study gestational age may have an effect on the presence of nuchal cord (p<0.05). Out of 64 cases with nuchal cord’, 11.4% of cases had meconium stained liquor present. 9.8% of cases with nuchal cord had FHR irregularity, which was significantly less as compared to 20.0% of cases who did not show FHR irregularity. This was statistically significant. (p=0.032). 18.7% of mother who showed presence of nuchal cord had delivery by caesarean section. 22.7% of cases with nuchal cord had NICU admissions, which was insignificantly more as compared to 17.0% of cases who did not have NICU admissions. Conclusions: Intrapartum events such as meconium staining of liquor and foetal heart rate irregularities were more commonly associated with nuchal cord but it did not affect the perinatal outcome. However, the mode of delivery was independent of the presence of nuchal cord, thereby reducing the morbidity to the mother. Hence nuchal cord is not associated with adverse perinatal outcomes and the presence of a nuchal cord per se is not found to be an indication of operative delivery.